Optimal computation of distance relays second zone timing in a mixed protection scheme with directional overcurrent relays. - Perez, L.G (IEEE Transactions on power delivery)
This paper describes a technique to determine the optimal time setting for the second zone of distance relays when used in a mixed protection scheme with directional overcurrent relays. The technique consists of including the second zone operation time as a new variable in the original problem statement of optimal computation of directional overcurrent relays settings. It is shown that the influence of distance relays and directional overcurrent relays must be considered when the settings of these relays are computed. Numerical results obtained with the proposed method for a realistic power system are presented